An Open Letter of Support from the NZ Association of Scientists to science colleagues and their families affected by the Christchurch mosques terror attack - Hannah, Kate; Stevens, Craig (New Zealand Science Review, 2019)
As-Salaam-Alaikum Kia tau te Rangimarie May Peace Be Upon You Kia ora e hoa mā, Like the rest of the country, the New Zealand Association of Scientists is devastated by the Christchurch mosques terror attack. At this time, we want to wrap our Muslim whānau – our colleagues and their families working or studying in science, social science, and the humanities – with aroha. As many of us moved from joyously engaging with direct action promoting climate justice, led by our rangitahi (youth), on the morning of Friday 15 March, to despair as a racist, anti-Islamic act of evil was committed, the best and worst of how people can be was brought into high relief. Our thoughts and support are offered to those who are affected and those who grieve with them. The relationship between science and religion is often considered to be complex. However, what remains absolutely clear at this time is that all people have a right to their beliefs and to carry them out as part of their community – of our community. On the 15th of March a sector of our community, our whānau, was attacked because of these beliefs. They receive our compassion, support, and understanding. The science community is an international one – filled with people from all backgrounds. In many cases these people, our science whānau, have travelled great distances with a view to improving the lives of themselves and their families. In doing so, they contribute to science and the science community in any number of ways. The New Zealand Association of Scientists commits, once again, to supporting the aspirations and careers of all scientists in Aotearoa New Zealand, and to speaking up on the issues which clearly affect them. As an Association, we have a statement of purpose around exposing pseudo-science, debating and influencing government science policy, and improving working conditions for scientists, including gender and ethnic equality. The extent to which these have directly addressed the issues of anti-Islamic sentiments and the so-called ‘Alt-Right’ is now revealed as inadequate – though they attest to our commitment to speak the truth and expose lies. In the coming weeks and months, we will work with colleagues throughout research and academia in Aotearoa New Zealand, particularly Muslim researchers, to develop resources on and protocols for dealing with the many issues this horrendous terrorist attack raises. Ngā mihi Kate Hannah and Craig Stevens on behalf of the NZAS President and Council